Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Budaya Organisasi Terhadap Loyalitas Karyawan Pada PT Gemilang Prasada Abadi - Andi Yusuf andi; Yoga Adiyanto Adiyanto; Syamsudin Syamsudin; Ahmad Firdaus; Dhany Isnaeni Darmawan (Jurnal Akuntansi Manajemen (JAKMEN), 2024)
This research aims to determine the influence of leadership style, work environment and organizational culture on employee loyalty at PT Gemilang Prasada Abadi. This research is a replication study using a quantitative approach method. The population of this study was 69 people. The sample was taken using a saturated sample of 69 respondents. Data was obtained from the results of distributing questionnaires to respondents. This research analysis uses multiple linear regression analysis with the results of the analysis showing the influence of leadership style, work environment and organizational culture on employee loyalty at PT Gemilang Prasada Abadi which is proven by the t test which shows t-count > t-table. The results of the f test analysis show that the influence of leadership style, work environment and organizational culture at PT Gemilang Prasada Abadi has a simultaneous effect on employee loyalty. This can be proven from the results of the f test by paying attention to the F-count > F-table value. And the significance value is <0.05. The concentration of this research is on employee loyalty which is influenced by leadership style, work environment and organizational culture. Suggestions for further research are expected to be able to retest based on dimensions and indicators other than those examined in this research.